Trade typhoon over Japan: Turbulence metaphor and spatial production cycles feedback loops of the Japanese economy, 1980–85–90 - M. Sonis; G. J. D. Hedwings; Y. Okuyama (Discrete Dynamics in Nature and Society)
This paper deals with the turbulence similitude between whirlpool structure of atmosphere disturbances and the spatial production cycles. Such an analogy leads to the production cycles feedback loops superposition analysis of trade feedbacks reflecting the economic phenomena of horizontal and vertical trade specifications. Moreover, the visualization of this process is achieved with the help of coloring the different permutation matrices presenting the hierarchy of production cycles feedback loops. In this manner the qualitative presentation of Japan inter-regional and inter-industry trade, 1980–85–90, is visualized and interpreted.